2019
DOI: 10.1155/2019/7306204
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Intubation Methods in Difficult Airways during Simulated Cardiopulmonary Resuscitation with Continuous Chest Compression: A Randomized Cross-Over Manikin Trial

Abstract: Introduction. Airway management is one of key elements of resuscitation. Endotracheal intubation is still considered the gold standard for airway management during resuscitation. Aim. The aim of the study was to compare success rates and intubation time of different endotracheal intubation methods during emergency intubation with difficult airways in the conditions of cardiopulmonary resuscitation in a standardized manikin model. Methods. The study was designed as a prospective, randomized, cross-over simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Case reports have suggested that the flexible tip of a videobronchoscope (fiberscope) can prevent ETT impingement on the trachea [ 14 , 15 ], and a prospective clinical trial showed that a flexible tip ETI (fiberscope) was superior to a preshaped stylet [ 6 ]. A comparison of the FROVA and the FTB with experienced intubators using the GlideScope showed faster and easier intubation with the FTB [ 7 ], and another manikin study using a MacIntosh laryngoscope showed superiority of the FTB during simulated cardiac arrest [ 16 ]. The FTB provides a cheaper, accessible alternative to the fiberscope, requiring only one intubator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Case reports have suggested that the flexible tip of a videobronchoscope (fiberscope) can prevent ETT impingement on the trachea [ 14 , 15 ], and a prospective clinical trial showed that a flexible tip ETI (fiberscope) was superior to a preshaped stylet [ 6 ]. A comparison of the FROVA and the FTB with experienced intubators using the GlideScope showed faster and easier intubation with the FTB [ 7 ], and another manikin study using a MacIntosh laryngoscope showed superiority of the FTB during simulated cardiac arrest [ 16 ]. The FTB provides a cheaper, accessible alternative to the fiberscope, requiring only one intubator.…”
Section: Discussionmentioning
confidence: 99%
“…Sharma outlined the limitations of GlideScope "intubation" as opposed to "laryngoscopy", suggesting that the two should be considered separately [19]. Previous comparative manikin studies include laryngoscopy time, measuring the time the blade enters the mouth until the ETT is fully inserted [12,16,20]. By excluding laryngoscopy and providing a static, constant view of the larynx, we provided the same view for each participant in both arms of the crossover study.…”
Section: Limitationsmentioning
confidence: 99%
“…The nine remaining studies had their reference lists screened and a further four studies were identified and included. A total of 13 studies were therefore included in our qualitative synthesis [14][15][16][17][18][19][20][21][22][23][24][25][26]. Of these studies, 10 were included in our quantitative synthesis [14,15,[19][20][21][22][23][24][25][26].…”
Section: Study Selectionmentioning
confidence: 99%
“…A total of 13 studies were therefore included in our qualitative synthesis [14][15][16][17][18][19][20][21][22][23][24][25][26]. Of these studies, 10 were included in our quantitative synthesis [14,15,[19][20][21][22][23][24][25][26]. This study selection process has been summarised in a PRISMA flow chart (Fig.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation